Evaluating the mechanisms of change in motivational interviewing in the treatment of mental health problems: A review and meta-analysis. (June 2015) - Romano, Mia; Peters, Lorna
Abstract: Motivational interviewing (MI) has proven useful in the treatment of a variety of mental health problems, however the mechanisms of MI's success within these populations remain unknown. This review is a first attempt to investigate and meta-analyse MI mechanisms of change research conducted with participants who suffer mood, anxiety, psychotic, eating disorders, and comorbid conditions. Twenty studies met inclusion criteria and examined a range of potential MI mechanisms, including patient motivation and confidence, patient resistance, and engagement. Results indicated that while MI did not increase patient motivation more so than did comparison conditions, MI showed a favourable effect on patient engagement variables. However, medium to high levels of heterogeneity were detected for patient engagement, indicating significant differences between studies. Heterogeneity was somewhat explained through subgroup analyses examining the effect of comparison condition and participant diagnosis. Overall, there were few MI mechanisms of change available for review, though the results suggest that patient engagement with treatment may be a potential mechanism of change in populations diagnosed with anxiety, mood, and psychotic disorders. Highlights: Motivational interviewing (MI) is useful in the treatment of a variety of mental health problems. Previous meta-analyses of MI mechanisms of change are limited to substance using populations. This review examined change mechanisms in patients diagnosed with anxiety, mood, eating, psychotic, and comorbid conditions. Research should further examine MI mechanisms of change in diverse populations.